1996
DOI: 10.1080/00207239608711060
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in the grouper fishEpinephelus coioidesfrom the coast of Bahrain: an assessment of monthly and spatial trends

Abstract: Concentrations of Cu, Pb, Zn, Cd, Fe, Mn and Ni were determined in samples of the grouper fish Epinephelus coioides from four stations in Bahrain, Arabian Gulf. The analyses were performed using an atomic absorption spectrophotometer. The overall mean levels for Cd, Cu, Fe, Mn, Ni, Pb and Zn were 1.2, 3.9, 3.2, 2.2, 4.4, 10.8 and 499 μg g -1 wet weight, respectively. The general pattern of occurrence in order of decreasing concentration was Zn > Pb > Ni > Cu > Fe > Mn > Cd. The concentration of Zn was only sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
1
2
Order By: Relevance
“…The present study accept the finding of [13,25,28,38,57] and disagree with the results of [6]. Levels of selected heavy metals in Pinctada radiata collected from two oyster beds in Bahrain were determined by [57]. This study reported elevated levels of Pb and Cd that exceeded the recommended standards of the World Health Organization [4].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The present study accept the finding of [13,25,28,38,57] and disagree with the results of [6]. Levels of selected heavy metals in Pinctada radiata collected from two oyster beds in Bahrain were determined by [57]. This study reported elevated levels of Pb and Cd that exceeded the recommended standards of the World Health Organization [4].…”
Section: Discussioncontrasting
confidence: 59%
“…In this study, the Arabian Gulf environmental status was assessed based on studies conducted in Bahrain, Kuwait, Oman, Saudi Arabia, Qatar, and United Arab Emirates (UAE) during 1983 and 2011. The present study accept the finding of [13,25,28,38,57] and disagree with the results of [6]. Levels of selected heavy metals in Pinctada radiata collected from two oyster beds in Bahrain were determined by [57].…”
Section: Discussioncontrasting
confidence: 55%
“…The TEs concentrations are increased in marine ecosystems by human activities (8). Fish is considered as a good indicator for the long-term research about TEs contamination in the aquatic habitats (9) and many studies have been conducted on the TEs concentrations in different fish species (10,11). The Caspian Sea is the largest lake in the world (12,13).…”
Section: Introductionmentioning
confidence: 99%